Disruption of thyroid hormone levels by decabrominated diphenyl ethers (BDE-209) in occupational workers from a deca-BDE manufacturing plant. (November 2018) - Chen, Tian; Niu, Piye; Kong, Fanling; Wang, Yuwei; Bai, Yi; Yu, Dong; Jia, Jiaxin; Yang, Luping; Fu, Zhongjian; Li, Renbo; Li, Jingguang; Tian, Lin; et al.
Abstract: While there is some evidence that exposure to decabrominated diphenyl ethers (BDE-209) affects thyroid function, the results obtained to date have been inconsistent. No studies have been performed on workers in deca-BDE manufacturing who had a high level of exposure to BDE-209 and relatively little exposure to other contaminants. In the present study, the relationship between BDE-209 exposure and thyroid hormone in occupational workers from a deca-BDE manufacturing plant was investigated. The serum and urine levels of polybrominated diphenyl ethers (PBDEs) and serum thyroid hormones were measured in 72 workers recruited from the deca-BDE manufacturing plant. The associations between their thyroid hormone levels and their exposure to BDE-209 were examined using multiple linear regression models. Serum concentrations of BDE-209 ranged from 67.4 to 109, 000 ng/g lipid weight (lw), with a median of 3420 ng/g lw, contributing to 93.1% of the total PBDEs. The concentration of BDE-209 in urine was highly correlated with that in the serum ( r 2 = 0.440, p < 0.001), indicating that urine may be a good non-invasive biomonitoring medium of BDE-209 body burden in occupational workers. BDE-209 in the serum was significantly and positively correlated with total thyroxine (tT4, r = 0.270, p = 0.029) and marginally and positively correlated with total triiodothyronine (tT3, r = 0.232, p = 0.061) in all occupational workers after adjusting for gender, age, BMI, and occupational exposure duration. A 10-fold increase in the serum BDE-209 concentration was associated with an increase in tT4 (8.63 nmol/L) [95% confidence interval (CI): 0.930–16.3] and tT3 (0.106 nmol/L) [95% confidence interval (CI): −0.005-0.219], corresponding to the increase of 7.8% in tT4 level and 5.4% in tT3 level. Associations between urine BDE-209 levels and thyroid hormones were similar to the results for the serum levels. These findings offer new evidence for proving the thyroid disrupting effects of BDE-209, impacting the direction of hyperthyroidism. Highlights: PBDEs in paired serum and urine from workers in a deca-BDE manufacturing plant were assessed. High level of BDE-209 was detected in serum and urine and considerably higher than those in other studies to date. Urine can be used to assess the internal exposure to BDE-209 in an occupational population. BDE-209 in serum was significantly and positively associated with total thyroxine and total triiodothyronine. Exposure to BDE-209 could disrupt thyroid hormone function with impacts in the direction of hyperthyroidism.